How Has Covid-19 Pandemic Influenced Online Exam Cheating in Some Countries? - Yousif ABDELRAHIM (Communications of International Proceedings, 2021)
This study endeavors to know the effects of the COVID-19 Pandemic on University and college students' online exam dishonesty (i.e., e-cheating) throughout the COVID-19 lockdown amongst university students in Bangladesh during 2020. The author collected the initial data from twenty-three undergraduate college students (ten females and thirteen males ) who voluntarily answered questions in a semi-structured interview through Messenger. The author used grounded theory and found that the lockdown throughout the COVID-19 quarantine has produced and enhanced levels of stress and anxiety amongst students, and therefore, has elevated online cheating. The anxiety and stress enable students to defend their dishonesty on online exams. The study conclusions also display numerous factors that have added to online exam deception. These constituents involve academic pressure, peer pressure, social pressure, not using software applications that regulate e-cheating, finding it effortless to cheat, eagerness to acquire grade point averages(GPA), and concerns about employment. Additionally, this research also reveals a COVID-19 online cheating conceptual model that describes how COVID-19, anxiety, and stress predict the recurrence of unethical behaviors among students, particularly cheating throughout online exams. The newly developed theoretical framework could be used for additional quantitative research investigations. Ultimately, faculty members can utilize the study outcomes as guidelines while considering online exams, homework, assignments, and monitoring online exams.
Keywords: Online Cheating; Anxiety; Stress; COVID-19.